Overview Of Customer Engagement In The Community Of Padang City During The Covid-19 Pandemic - Frihapma Semita Ade; Ria Okfrima; Krisnova Nastasia (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The Covid-19 pandemic has caused many impacts on various sectors of life. There are many changes in habits occur in education, offices, economy, trade and many other sectors. In the economic sector, many business actors complain about the change in habits that interact directly to become connected via the internet network. Many businessmen have complained about the decreasing their income due to this pandemic and there are a lot that has been forced to permanently stop their business activities. Even so, there are still many businessmen who are still able to survive in the midst of this pandemic. They can still attract the attention of their consumers and do various ways to keep these consumers using their products. This situation is called customer engagement, which is a condition where consumers/customers feel psychologically bound/involved in the products they use. Thus, the researchers here are interested in seeing how the customer engagement picture of the people of Padang City during the covid-19 pandemic describes. The method used in this research is descriptive quantitative research method. Data were obtained using a psychological scale in the form of a questionnaire totaling 31 statement items. The results of research on 210 people show that the level of customer engagement of the people of Padang City during the Covid19 pandemic is relatively low. People do not have a high attachment or do not stick to one product, but there are other things that influence people in buying and using a product, namely the urgent need and the price given. It indirectly shows that the pandemic has had a significant impact on community customer engagement. The results of additional statistical analysis also show that differences in gender and type of work also affect the formation of community customer engagement.